2019
DOI: 10.1038/s41588-019-0477-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of BAF mutations provides insights into intracomplex synthetic lethalities in human cancers

Abstract: Aberrations in genes coding for subunits of the BAF chromatin remodeling complexes are highly abundant in human cancers. Currently, it is not understood how these loss-of-function mutations contribute to cancer development and how they can be targeted therapeutically. The cancer-typespecific occurrence patterns of certain subunit mutations suggest subunit-specific effects on BAF complex function, possibly by the formation of aberrant residual complexes. Here, we systematically characterize the effects of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 59 publications
9
127
1
Order By: Relevance
“…Compared with genes for which intron targeting sgRNAs did not result in isolation of GFP-positive cells, successfully targeted genes have higher average expression in HAP1 cells ( Fig. 1E; Schick et al 2019). By single-cell dilution, we then isolated 335 clonal cell lines for which a massively parallel multiplex sgRNA amplicon sequencing strategy unambiguously identified the integrated sgRNAs indicating a single tagged protein (Supplemental Note S1; Supplemental Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with genes for which intron targeting sgRNAs did not result in isolation of GFP-positive cells, successfully targeted genes have higher average expression in HAP1 cells ( Fig. 1E; Schick et al 2019). By single-cell dilution, we then isolated 335 clonal cell lines for which a massively parallel multiplex sgRNA amplicon sequencing strategy unambiguously identified the integrated sgRNAs indicating a single tagged protein (Supplemental Note S1; Supplemental Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Although we could show that knockout efficiency is only slightly decreased in diploid compared to haploid HAP1 cells, the effect is considered to be stronger in polyploid cancer cell lines where a full knockout requires out-of-frame editing of all alleles of a gene (Van Campenhout et al 2019) . HAP1 cells with specific gene knockouts have therefore been applied in many studies addressing various research questions (Davis et al 2015;Schick et al 2019;Lenk et al 2019;Smits et al 2019;Gerhards et al 2018;Baggen et al 2019) . The exact cellular context of this cell line is, however, not fully understood, especially since HAP1 cells do not share major characteristics with their parental chronic myeloid leukemia (CML) cell line KBM7.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive analysis of synthetic lethality between 2 factors in all subunits of the SWI/SNF chromatin remodeling complex showed that the SMARCA4‐ARID2, SMARCA4‐ACTB, and SMARCC1‐SMARCC2 pairs are significant for synthetic lethality . Considering synthetic lethality among these pairs, the SMARCA4 and ARID2 relationship would be a potential target for synthetic lethal therapy because SMARCA4 and ARID2 are frequently mutated in cancer.…”
Section: Synthetic Lethal Targets Based On Targeting the Interaction mentioning
confidence: 99%